Computational Homogenization of Micromechanically Resolved Textile Materials - Mehnert, Markus; Fillep, Sebastian; Mergheim, Julia; Steinmann, Paul (2015)

Computational homogenization of one-dimensional textile structures - Fillep, Sebastian; Mergheim, Julia; Steinmann, Paul (Proceedings of the 7th International Conference on Textile Composites and Inflatable Structures, STRUCTURAL MEMBRANES 2015, 2015)
In this contribution a computational homogenization method for one-dimensional technical textiles, i.e. ropes or cables, is developed. Regarding the large length-tothickness ratio that characterizes rope-like textiles on the macro level, a discretization with beam elements is numerically efficient. The homogeneous macro level is influenced by the heterogeneous micro structure involving contact between the fibers. Therefore, the fibers are modeled explicitly a representative volume element to capture the contact within interactions. For the connection of the two scales a specific homogenization method is introduced involving theoretical aspects and numerical examples for periodic rope-like structures.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Beam; Computational homogenization; Contact; Technical textiles

Computational homogenization of rope-like technical textiles - Fillep, Sebastian; Mergheim, Julia; Steinmann, Paul (Computational Mechanics, 2015)
This contribution investigates a computational homogenization method for one-dimensional technical textiles i.e. ropes or cables. On the macroscopic level rope-like textiles are characterized by a large length-to-thickness ratio, such that a discretization with structural elements, i.e. beam elements, is numerically efficient. The material behavior is, however, strongly influenced by the heterogeneous micro structure. Here, the fibers at the micro structure are modeled explicitly via a representative volume element whereby the contact interactions between fibers are captured. To transfer the microscopic response to the macro level a beam specific homogenization scheme is introduced. Theoretical aspects are discussed, e.g. the advocated beam specific power averaging theorem and the corresponding scale transition, and numerical examples for periodic rope-like structures are given.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-TM.comput
Keywords: Beam kinematics; Computational homogenization; Contact; Ropes; Technical textiles

Computational modelling and homogenization of technical textiles - Fillep, Sebastian; Mergheim, Julia; Steinmann, Paul (Engineering Structures, 2013)
This contribution presents a multiscale homogenization method to model technical textiles. On the macroscopic level textiles are characterized by a large area-to-thickness ratio, such that a discretization with shell elements is numerically efficient. The material behavior is strongly influenced by the heterogeneous (e.g. woven) microstructure. This is explicitly modelled by means of a volumetric microsample, and a homogenization scheme is applied to transfer the microscopic response to the macrolevel. Theoretical aspects are discussed and a numerical example for periodic textile structures is given. © 2013 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-TM.comput
Keywords: Homogenization; Multi scale; Shell kinematic; Technical textiles

Homogenization and modelling of technical textiles - Fillep, Sebastian; Mergheim, Julia; Steinmann, Paul (European Congress on Computational Methods in Applied Sciences and Engineering Proceedings, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-TM.homoge_5

Homogenization in periodically heterogeneous elastic bodies with multiple micro contact - Fillep, Sebastian; Orlik, Julia; Bare, Zoufine; Steinmann, Paul (Mathematics and Mechanics of Solids, 2013)
The aim of this contribution is to compute the effective in-plane tension and shear behaviour of textile-like elastic materials, that is, plates or  shells with a periodic micro-structure composed of long woven or  knitted fibres. The knitting or weaving results in multiple periodic  contact between fibres. Mathematically the problem can be formulated as anin-plane elasticity problem defined in a heterogeneous domain with ε-periodic micro-structure, including multiple micro-contact between the structural components, which is described by the  Signorini and Tresca-friction contact conditions.The asymptotic  analysis and homogenized limit for such problems was recently obtained by Damlamian et al. via periodicunfolding strategy. These  results are briefly recalled in the paper. The obtained two-scale  algorithm is implemented for some specific textile materials, which are macroscopic shells with a 3-D microstructure including contact. For  each  macroscopic deformation state, a contact problem in the  periodicity  cell or representative volume element is solved and the  corresponding non-linear macroscopic stress–strain relation is   obtained. The results are illustrated by the simulation of woven and knitted textiles.
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-TM.homoge_38
Keywords: Contact problems; effective elasto-plasticity; textile structures

Homogenization of heterogeneous, fibre structured materials - Fillep, Sebastian; Mergheim, Julia; Steinmann, Paul (COMPLAS XII - XII Inernational Conference on Computational Plasticity. Fundamentals and Applications, 2013)
This contribution presents a multi-scale homogenization method to model fibre structured materials. On the macroscopic level textiles are characterized by a large area-to-thickness ratio, such that a discretization with shell elements is numerically efficient. The material behavior is strongly influenced by the heterogeneous micro structure. To capture the contact on the micro level, the RVE is explicitly modelled by means of a volumetric micro sample and a shell specific homogenization scheme is applied to transfer the microscopic response to the macro level. Theoretical aspects are discussed and a numerical example for contact behavior of a periodic knitted structure is given.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-TM.homoge
Keywords: Contact; Homogenization; Hysteresis; Multi-scale; Shell kinematic; Technical textiles

Microscale modeling and homogenization of rope-like textiles - Fillep, Sebastian; Mergheim, Julia; Steinmann, Paul (Proc. Appl. Math. Mech., 2014)
UnivIS-Import:2015-10-26:Pub.2014.tech.FT.FT-TM.micros

Microscale modelling and homogenization of fiber structured materials - Fillep, Sebastian; Steinmann, Paul (Proceedings of Applied Mathematics and Mechanics (PAMM), 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-TM.micros_4

On the homogenization of technical textiles - Fillep, Sebastian; Mergheim, Julia; Steinmann, Paul (Bytes and science, 2012)
UnivIS-Import:2015-10-26:Pub.2012.tech.FT.FT-TM.ontheh

Towards an efficient two-scale approach to model technical textiles - Fillep, Sebastian; Mergheim, Julia; Steinmann, Paul (Computational Mechanics, 2017)
The paper proposes and investigates an efficient two-scale approach to describe the material behavior of technical textiles. On the macroscopic scale the considered textile materials are modeled as homogeneous by means of shell elements. The heterogeneous microstructure, which consists e.g. of woven fibers, is explicitly resolved in representative volume elements (RVE). A shell-specific homogenization scheme is applied to connect the macro and the micro scale. The simultaneous solution of the macroscopic and the nonlinear microscopic simulations, e.g. by means of the FE2-method, is very expensive. Therefore, a different approach is applied here: the macro constitutive response is computed in advance and tabulated for a certain RVE and for different loading scenarios. These homogenized stress and tangent values are then used in a macroscopic simulation without the need to explicitly resort to the microscopic simulations. The efficiency of the approach is analyzed by means of numerical examples.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Computational homogenization; Shell kinematics; Tabulated macro constitutive model; Tangent calculation; Technical textiles